Modernism à la mode : fashion and the ends of literature - Sheehan, Elizabeth M. (Cornell University Press, 2018)
"This book puts the work of early twentieth-century texts in conversation with twenty-first-century theories of affect, materiality, animality, beauty, and history and explores how fashion describes the limits and possibilities for modernist aesthetic and political transformation"--